Results of Standard Stapler Closure of Pancreatic Remnant After Distal Spleno-Pancreatectomy for Adenocarcinoma - Illuminati, Giulio; Cerasari, Saverio; Pasqua, Rocco; Nardi, Priscilla; Fratini, Chiara; Frey, Sébastien; Iannelli, Antonio; Marini, Pierluigi (Frontiers in Surgery, 2020)
Background/aim: The purpose of this study was to evaluate the results of stapled closure of the pancreatic remnant after cold-knife section of pancreatic isthmus and distal pancreatectomy for adenocarcinoma. Methods: Retrospective evaluation of 57 consecutive patients undergoing distal spleno-pancreatectomy (DP) for adenocarcinoma. The pancreatic isthmus was systematically straight sectioned with a cold knife and the remnant was stapler closed without additional stitches or adjuncts. Study’s main endpoints were postoperative mortality, the occurrence of a pancreatic fistula, the need for re-operation, postoperative length of stay in the hospital, rate of re-admission and late survival. Results: Postoperative mortality was absent. Seventeen patients (29.8 %) presented a pancreatic fistula, of grade A in 7 case (41.2 %) , grade B in 8 cases (47.1%) and grade C in 2 case (11.8%). Reoperation was required in the two patient (3.5 %) with grade C fistula in order to drain an intraabdominal abscess. The mean postoperative length of stay in the hospital was 15 days (range, 6 - 62 days). No patient required readmission. Twentynine patients (50.8 %) were alive and free from disease, respectively 12 patients (21.1 %) at 12 months, 13 patients (22.8 %) at 60 and 4 patients (7.0 %) at 120 months from the operation. The remaining patients died of metastatic disease 9 to 37 months from the operation. Late, disease related mortality was 49.1 %. Conclusion: Stapler closure of the pancreatic remnant allows good postoperative results, limiting the formation of pancreatic fistula to the lower limit of its overall reported incidence.